EXPLORATION OF ENGLISH LEARNING PRACTICES WITH EDTECH AND LOCAL CULTURE AMONG MANDAR YOUTH - Amrang Amrang; Hustiana Hustiana (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2025)
Abstract: This study explores English language learning practices that integrate educational technology (EdTech) and Mandar local culture among the younger generation in coastal areas of West Sulawesi, Indonesia. Employing an exploratory qualitative approach, data were collected through non-participant observations and semi-structured interviews with 20 students and two English teachers. The research framework combined Engeström’s Cultural-Historical Activity Theory (E-CHAT) for classroom observations and the TPACK framework for analyzing teachers’ integration of technology, pedagogy, and content knowledge. Findings indicated that while teachers actively facilitated learning and employed simple technologies such as YouTube, Canva, and LCD projectors, the integration of local culture remains minimal and mostly indirect. Teachers adapted pedagogical strategies to students’ characteristics through game-based learning, translanguaging, differentiated instruction, and peer collaboration. Technology enhanced student engagement and comprehension, particularly through visual and interactive media, though its use is constrained by limited internet access, device availability, and teacher training. Incorporating Mandar cultural elements, such as folktales, traditional practices, and vocabulary, showed potential to make learning more contextual, meaningful, and motivating, fostering both language proficiency and cultural awareness. The study highlights the importance of targeted professional development and infrastructural support to optimize EdTech integration, and provides insights for educators and policymakers to design culturally grounded, technology-enhanced English learning approaches that are both globally relevant and locally meaningful.